REVOLUTIONIZING MEDICINE: A COMPREHENSIVE REVIEW OF MODERN DIAGNOSTIC TECHNOLOGIES - Asatullyev Rustam Baxtiyorovich; Qilichbayeva Malikabonu Uchqunjon qizi (TADQIQOTLAR, 2026)
Abstract: Diagnostic technologies are the cornerstone of modern medicine, enabling the accurate detection, characterization, and monitoring of human diseases. This article provides a systematic overview of major diagnostic modalities, including medical imaging (X-ray, computed tomography, magnetic resonance imaging, ultrasound, and nuclear medicine), molecular diagnostics (polymerase chain reaction, next-generation sequencing, and biosensors), point-of-care technologies, and emerging fields such as liquid biopsy and artificial intelligence-assisted diagnosis. The article discusses the principles, clinical applications, advantages, and limitations of each technology. Special attention is given to the role of diagnostic technologies in early disease detection, personalized medicine, and infectious disease outbreaks, including the COVID-19 pandemic. The review concludes with an analysis of current challenges—such as cost, accessibility, and data integration—and future directions, including lab-on-a-chip devices and wearable diagnostics.